(untitled) (ARQUISUR Revista, 2020)
This paper investigates the effects of street alignment buildings and different front setbacks on the perception of the aesthetics of the public open space according to groups of people with different levels and types of educational background. The study was carried out in the Cidade Baixa neighborhood, Porto Alegre/RS, from the selection of six interfaces with the following characteristics: buildings with different alignments (maximum 6m); buildings aligned and set back (maximum 6m) in relation to the public sidewalk and buildings in alignment with the public sidewalk. Data were collected through questionnaires for residents of Porto Alegre / RS. The results indicate a greater appreciation of architects for orderly buildings and with a direct relationship with the street, while non-architects gave greater preference to the existence of front setbacks and vegetation.